Quality Assessment and Patient-Reported Outcomes Integration Framework for Chronic Disease Survivorship Research - Chinonso Gerald Udensi,; Opeoluwa Oluwanifemi Akomolafe,; Christiana Adeyemi, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
Chronic disease survivorship research increasingly recognizes the need for comprehensive frameworks that integrate both objective clinical outcomes and subjective patient experiences to enhance long-term care quality. This paper proposes a Quality Assessment and Patient-Reported Outcomes (PROs) Integration Framework tailored for chronic disease survivorship, addressing the multidimensional nature of survivorship trajectories. The framework is grounded in the intersection of evidence-based quality metrics, standardized PRO instruments, and adaptive data analytics, enabling researchers and healthcare providers to capture holistic patient health profiles. Quality assessment components encompass clinical performance indicators, adherence to evidence-based guidelines, continuity of care, and outcome benchmarks aligned with national and international standards. Parallel to these, PRO measures covering physical functioning, symptom burden, emotional well-being, social participation, and health-related quality of life are systematically collected and validated using psychometrically robust tools. The integration process leverages interoperable health information systems and advanced analytical models to merge quality metrics with PRO datasets, enabling real-time monitoring, predictive modeling, and personalized care adjustments. A cyclical feedback mechanism ensures that insights derived from PROs directly inform quality improvement initiatives and care pathway optimization. Furthermore, the framework addresses methodological challenges such as missing data, measurement equivalence across diverse populations, and longitudinal tracking over extended survivorship periods. Ethical considerations, including patient autonomy, informed consent, and data governance, are embedded to maintain trust and transparency. By uniting quantitative quality assessment with qualitative patient narratives, the proposed framework provides a nuanced understanding of survivorship outcomes, empowering stakeholders to identify care gaps, optimize interventions, and advance health equity. Its adaptability across various chronic conditions including cancer, cardiovascular disease, diabetes, and autoimmune disorders positions it as a versatile tool for translational research and health policy development. The framework fosters patient-centered research practices that align with global calls for integrated outcome measurement, ultimately contributing to improved survivorship care quality and sustained patient well-being.
Keywords: Chronic Disease Survivorship; Quality Assessment; Patient-Reported Outcomes (Pros); Health-Related Quality Of Life; Survivorship Research; Care Pathway Optimization; Outcome Measurement; Health Equity; Integrated Framework; Patient-Centered Care